A new model of application response time for VoIP over WLAN and fixed WiMAX - Nisar, K. (Institute of Electrical and Electronics Engineers Inc., 2015)
The Voice over Internet Protocol (VoIP) and Wireless Local Area Networks (WLANs) has observed the fastest growth in the world of communication. The WLAN is the most assuring of technologies among the wireless networks, which has facilitated high-rate voice services at low cost and good flexibility over IP-based networks. Worldwide Interoperability for Microwave Access (WiMAX) technology is also a preliminary step to develop Fourth Generation networks (4G) technologies. WiMAX is a recent wireless broadband standard that has promised high bandwidth over long-range transmission. The standard specifies the air interface, including the Medium Access Control (MAC) and Physical (PHY) layers, of Broadband Wireless Access (BWA). It has not only succeeded in the utilization of several of the latest telecommunication techniques in the form of unique practical standards, but also paved the way for the quantitative and qualitative developments of high-speed broadband access. The Institute of Electrical and Electronics Engineers (IEEE 802.16) Standard introduces several advantages; one of them is support for Quality of Services (QoS) at the Media Access Control (MAC) level. However, the existing VoIP over WLAN and WiMAX architecture does not provide sufficient QoS in both networks. In this paper we provide an overview and develops a new distributed model to improve QoS performance for VoIP over WLAN and Fixed WiMAX network with respect to Application Response Time (ART). The model was simulated in the OPNET modeler (16.0) with Multiple Access Points (APs), Base Stations (BSs)as well as mobile devices, Subscribers Stations (SSs), and some server BSs that were selected based on Nearest Neighborhood Algorithm and Orthogonal Frequency Division Multiplexing (OFDM) techniques. The results obtained from this proposed model showed significant performance in network application response time. Â© 2015 IEEE.